Antibiotic Susceptibility Patterns of Gut Microbiota in Inflammatory Bowel Disease - Varshitha, Kondakindi; Ingle, Rutuja Prakash; Fatima, Naaz; Sharma, Aditya; Bhavani, Konde Tulja; Jabeen, Arshiya; Jahan, Noor; Koureti, Prince; Singh, Jagjeet; Sharma, Narotam; et al. (Journal of Neonatal Surgery, 2025)
Inflammatory bowel disease (IBD) involves inflammation of the digestive tract and intestines. This inflammation leads to the development of ulcers and causes discomfort during bowel movements. The primary contributors to IBD are poor dietary habits and a lack of physical activity. Inflammation occurs from mouth to anus because of toxic substances released by the bacteria into the system. This study focuses on the antibiotic resistance and susceptibility of the microorganisms that cause IBD. The methodology is based on earlier research related to ASMR and ASPR. Utilizing data till 2019, predictions of IBD incidence for the future in India are provided. The results of the antibiotic sensitivity disc test for the positive samples in the study indicate resistance and susceptibility to specific microorganisms linked to IBD. Statistical analysis shows that India accounts for 8% of global IBD cases annually. More than 37,000 cases have been reported in India. Various regions in newly industrialized countries face an increased risk of developing IBD. Reports from 2019 indicate that males are more frequently affected than females. The prevalence of the disease is higher than the mortality rate among patients, which stands at 20.34%. From this study, in 2025 the males are more affected than females, which stands at 41.25%..